2012
DOI: 10.1021/jm300396n
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Guided Design of A3 Adenosine Receptor-Selective Nucleosides: Combination of 2-Arylethynyl and Bicyclo[3.1.0]hexane Substitutions

Abstract: (N)-Methanocarba adenosine 5′-methyluronamides containing known A3 AR (adenosine receptor)-enhancing modifications, i.e. 2-(arylethynyl)adenine and N6-methyl or N6-(3-substituted-benzyl), were nanomolar full agonists of human (h) A3AR and highly selective (Ki ~0.6 nM, N6-methyl 2-(halophenylethynyl) analogues 13, 14). Combined 2-arylethynyl-N6-3-chlorobenzyl substitutions preserved A3AR affinity/selectivity in the (N)-methanocarba series (e.g. 3,4-difluoro full agonist MRS5698 31, Ki 3 nM, human and mouse A3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
244
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(252 citation statements)
references
References 59 publications
7
244
0
Order By: Relevance
“…The C2 group of 20 was accommodated in an exofacial interface region generated by the outward movement of TM2 in the hybrid A 3 AR model, as previously proposed for derivatives bearing rigid and extended C2 substituents. 12,13 Thus, the major conserved recognition points for A 3 AR agonists were preserved in the 1-deaza analogues, and as expected, the N1 of adenosine is not required for binding. Several different N 6 substitutions can be tolerated in this series, slightly modulating the affinity depending on their accommodation in a region a Effect shown for ipsilateral hind paw; there is no effect on the contralateral side.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 66%
“…The C2 group of 20 was accommodated in an exofacial interface region generated by the outward movement of TM2 in the hybrid A 3 AR model, as previously proposed for derivatives bearing rigid and extended C2 substituents. 12,13 Thus, the major conserved recognition points for A 3 AR agonists were preserved in the 1-deaza analogues, and as expected, the N1 of adenosine is not required for binding. Several different N 6 substitutions can be tolerated in this series, slightly modulating the affinity depending on their accommodation in a region a Effect shown for ipsilateral hind paw; there is no effect on the contralateral side.…”
Section: Acs Medicinal Chemistry Letterssupporting
confidence: 66%
“…of Gly105 in EL1 of b 1 AR and the lack of a Gly residue at the aligned position in EL1 of b 2 AR likely contribute to the difference in the flexibility of the extracellular portion of the TM2 Prokink between b 1 AR and b 2 AR, in a manner highly analogous to that observed in D3R and D2R. Similarly, modeling studies of the A 3 adenosine receptor in complex with an agonist containing rigid C2 extensions have suggested that an outward displacement of TM2 is required to accommodate such a bulky ligand (Tosh et al, 2012). Prior chimeric receptor and mutagenesis studies were consistent with a contribution of a region containing EL1 and, to a much lesser degree, EL2, in D3R over D2R selectivity for R-22 (Newman et al, 2009) and another highly D3R-selective F-analog of R-22 (Banala et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…Various sterically constrained adenine nucleoside derivatives (Supplemental Material; (Supplemental Table 1) (Table 1) have been synthesized and studied for their potent binding to the A 1 AR (compound 2) (Tosh et al, 2012b) or A 3 AR (compounds 1, 3-9, 14-19, 21-28, 31, and 32) (Tosh et al, 2012a(Tosh et al, , 2015a. Many of these A 3 AR agonists reduce chronic neuropathic pain in a phenotypic screen, and the AR binding affinities of the previously reported nucleosides are provided (Supplemental Material; (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine analogs are under development as potential therapeutic agents for treating chronic neuropathic pain and other diseases (Tosh et al, 2012a;Borea et al, 2015;Little et al, 2015). Among these potent adenosine receptor (AR) agonists are the 9-riboside N 6 -(3-iodobenzyl)adenosine-59-N-methylcarboxamide (IB-MECA; Stoilov et al, 2014) and the carbocyclic (19S,29R,39S,49R,59S)-49-{2-chloro-6- [(3-iodophenylmethyl) amino]purin-9-yl}-1 (methylaminocarbonyl)-bicyclo[3.1.0] hexane-2,3-diol MRS1898 (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation